2017
DOI: 10.1016/j.jfluidstructs.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a hybrid morphing wing with active open loop vibrating trailing edge by time-resolved PIV and force measures

Abstract: et al.. Dynamics of a hybrid morphing wing with active open loop vibrating trailing edge by Time-Resolved PIV and force measures.This is an author-deposited version published in: http://oatao.univ-toulouse.fr/ Eprints ID: 16095Open Archive Toulouse Archive Ouverte (OATAO)OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Keywords:Morphing Smart materials Wind tunnel experiments Vortex breakdown Harmonic forcing a b s t r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 25 publications
(33 reference statements)
2
62
0
Order By: Relevance
“…This reduction of vortex shedding noise has been observed on a cylinder with flexible elements on the aft half of the cylinder (Kamps et al, 2016;Geyer et al, 2017). Jodin et al (2017) has showed that by using a similar, but active, trailing edge modification the wake structure is modified and it is this type of flow modification that is thought to be the mechanism behind the low frequency noise reduction. It can be seen that the reduction in the low frequency range has been scattered into the medium to high frequency range (∼ 1 kHz).…”
Section: Single Microphone Measurementsmentioning
confidence: 71%
“…This reduction of vortex shedding noise has been observed on a cylinder with flexible elements on the aft half of the cylinder (Kamps et al, 2016;Geyer et al, 2017). Jodin et al (2017) has showed that by using a similar, but active, trailing edge modification the wake structure is modified and it is this type of flow modification that is thought to be the mechanism behind the low frequency noise reduction. It can be seen that the reduction in the low frequency range has been scattered into the medium to high frequency range (∼ 1 kHz).…”
Section: Single Microphone Measurementsmentioning
confidence: 71%
“…This will highlight the effects coming from the vibrating trailing edge in the context of the hybrid morphing. The present article follows the experimental work of G. Jodin et al [5] for a Reynolds number of 1 million. The measurements will be compared with the numerical studies following to provide a validation of both approaches.…”
Section: Methodsmentioning
confidence: 87%
“…Currently, electroactive morphing is being studied and developed in the context of the European research program of H2020, "Smart Morphing & Sensing for Aeronautical configurations" (www.smartwing.org/SMS/EU). In particular, the hybrid morphing concept, partly bio-inspired, was introduced ([4], [5]) to operate at various time scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerodynamic performance enhancement and structural mass reduction have been introduced using morphing skill applied to airfoil camper Vale1 et al [5]. Jodin et al [6] have showed that vibrating the airfoil trailing edge with high frequency and little amplitude was capable of rising the lift and reducing the drag consequently. Vasista et al [7] have studied the wing tip droop-nose using morphing technique and explained experimentally the visions from tests and gave some recommendations also they were not envisioned to improve the wing aerodynamic loads coefficients.…”
Section: Introductionmentioning
confidence: 99%